Portuguese-Spanish interfaces : diachrony, synchrony, and contact - Amaral, Patrícia Matos, 1975-; Carvalho, Ana Maria (Issues in Hispanic and Lusophone linguistics., 2014)
Western hemisphere varieties of Spanish and Portuguese show substantial similarity in the patterning of sociolinguistic variation and change. Caribbean and coastal dialects of Latin American Spanish share several variables with Brazilian Portuguese (e.g., deletion of coda -s, -r). These variables also show similar social distribution in Hispanic and Lusophone communities: formal styles and high status speakers are consonantally conservative, while higher deletion is associated with working class speakers and informal styles. The regions that show these sociolinguistic parallels also share comm.